He Gave Me Wings... - Adegbola, Funso (BookBuilders, 2005)
This brief memoire by Funso Adegbola recounts a unique and special relationship of a daughter with her very famous Dad, Chief Bola Ige.
Keywords: Autobiography & Biographies( Nigeria); Memoirs; Non Fiction